Sustainable development : closing the loop - Kushwaha, Saket (Delve Publishing, 2021)
One of the most significant topics for the current time in history is sustainable development. It is a development that complies with the requirements of the present without barring the necessities and opportunities of forthcoming generations. Sustainable development is a diverse subject encompassing various disciplines, providing it both a pragmatic approach and a philosophical base. It focusses on a broad range of interests from corporations to nations to stakeholders because it syndicates environmental safety and economic development into a single system. Sustainable development is linked with the methods for development of long-term activities of humans guaranteeing the harmony of economic, ecological and social equilibrium. Sometimes, the risk associated with the violation of sustainable development principles are of diverse kinds. Nevertheless, the consequences of various unsustainable activities of human beings hurt the ecosystem badly and may impact the survival of upcoming generations. The underlying agenda of this book on sustainable development is to provide detail insight on the principles and prerequisites of sustainable development. In order for us to achieve sustainable development, it must be comprehensive, i.e., it should successfully balance social goals with environmental and economic perspectives.